Relationship Between Age and Parity of Birthing Mothers to the Incidence of Premature Rupture of Membranes at Bali Mandara Regional Hospital, Bali Province in 2022 - Sujiati Sujiati; Ni Luh Putu Sri Erawati; Ni Komang Yuni Rahyani (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2024)
Premature Rupture of Membranes (PROM) is an obstetric problem that occurs throughout the world and increases morbidity and mortality in mothers and babies. The prevalence ofPROM in Indonesia reaches 6.46-15.6%. A preliminary study at Bali Mandara Hospital showed a high prevalence of PROM over the past four years. The purpose of this study was to determine the relationship between the age and parity of birthing motherswith the incidence of PROM at Bali Mandara Hospital, Bali Province in 2022. This type of research is an analytical study with a cross-sectional design and uses simple random sampling on 117 birthing mothers as subjects. This study uses secondary data frompatient medical records. Univariate data are presented through frequency distribution, while bivariate analysis uses the Chi Square test with a significance level of Î± = 0.05. The results of the research analysis indicate a significant relationship betweenthe age of the birthing mother (p-value = 0.001) and the parity of the birthing mother (p-value = 0.003) with the incidence of PROM. Health workers, especially midwives, are expected to be able to provide education and improve pregnancy care services and pregnant women are advised to undergo routine pregnancy check-ups to reduce the risk of PROM and further researchers are expected to explore other risk factors related to PROM.